2021
DOI: 10.1111/vox.13219
|View full text |Cite
|
Sign up to set email alerts
|

The use of social media as a tool for patient blood management and transfusion medicine education

Abstract: Background and Objectives: Transfusion is one of the most performed medical procedures. Wrong indications are common and are probably related to the scarcity of transfusion teaching during medical education. The development of a new way to improve transfusion education is paramount. Social media has the potential to reach larger audiences for rapid communication of medical content. The use of social media for transfusion education in Brazil has not been published. The aim of this article is to describe a new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Physicians including interns/residents/foundational‐year trainees (six studies), medical students (six studies), and nurses/midwives (six studies) were the common targeted learners, followed by nursing/midwifery students and staff in the first year of training (four studies) and laboratory technologists/scientists students (one study). Three publications described targeting multiple healthcare professional learners 18,23,24 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Physicians including interns/residents/foundational‐year trainees (six studies), medical students (six studies), and nurses/midwives (six studies) were the common targeted learners, followed by nursing/midwifery students and staff in the first year of training (four studies) and laboratory technologists/scientists students (one study). Three publications described targeting multiple healthcare professional learners 18,23,24 …”
Section: Resultsmentioning
confidence: 99%
“…These reported positive impact on outcomes, such as a reduction in blood component ordering and transfusion rates, improved traceability, and improvement in perinatal outcomes related to postpartum hemorrhage. Brunetta et al evaluated the impact of its social media learning program and reported a reduction in RBC transfusions, and an increase in single‐unit RBC used after introducing the social media program 24 . Kelly et al introduced formal staff education including a transfusion e‐learning module, then retrospectively reviewed the overall transfusion and discard rates, indication, and the hemoglobin cut‐offs for transfusion orders in the emergency department 15 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations